Surviving Works: context in Verre arts Part Two, Chapter Five: Towards a Verre catalogue raisonnée 5.1: Percussive metals: bells, gongs, rattles. Issue 1 (2021) - Chappel, Tim; Fardon, Richard; Piepel, Klaus
No abstract available